The value of terroir: Hedonic estimation of Vineyard sale prices - Robin Cross; Andrew J. Plantinga; Robert N. Stavins (Fondazione Eni Enrico Mattei (FEEM), 2011)
We examine the value of terroir, which refers to the special characteristics of a place that impart unique qualities to the wine produced. We do this by conducting a hedonic analysis of vineyard sales in the Willamette Valley of Oregon to ascertain whether site attributes, such as slope, aspect, elevation, and soil types, or designated appellations are more important determinants of price. We find that prices are strongly determined by sub-AVA appellation designations, but not by specific site attributes. These results indicate that the concept of terroir matters economically, although the reality of terroir as proxied for by locational attributes is not significant.
Keywords: C2; Q11; 330; Wine; Vineyard; Weinbau; Boden; Region; Hedonischer Preisindex; USA